STUDI TENTANG KONSEP PENDIDIKAN IDEAL (Berkaca Pada Pola Pendidikan Islam Masa Rasulullah saw) - Muhlison Muhlison (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2018)
Near to say that nothing party doubting of, and surely to deny that education is represent the very required case by human being. Education cause represent one of factor which very strategic position and very role of signifikan in the effort develop;building civilization of human being to the prosperity live, either through individually and also by kolektiv. strive in order to finding  ideal format of education, efficient and effective, ever non-stoped to be onducted by various party which have competence. But in the middle of effort of various the party, is not rarely happened the polemic which often have implication to project unload the tide and patchwork model the itself education. Islam Education that executed at  Rasulullah saw era, representing ideal Islam education format, because have been practiced direct by the  byword guided by Allah swt, have to be non-stoped learned the, guidance and developed by Islam people during the time to avoid the polemic of Islam education non-stoped endless